Healthcare costs in patients with advanced non-small cell lung cancer and disease progression during targeted therapy: a real-world observational study. (1st February 2018) - Skinner, Karen E.; Fernandes, Ancilla W.; Walker, Mark S.; Pavilack, Melissa; VanderWalde, Ari
Abstract: Aims: To assess healthcare costs during treatment with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) and following disease progression in patients with advanced non-small cell lung cancer (NSCLC). Methods: A retrospective analysis of medical records of US community oncology practices was conducted. Eligible patients had advanced NSCLC (stage IIIB/IV) diagnosed between January 1, 2008 and January 1, 2015, initiated treatment with erlotinib or afatinib (first-line or second-line), and had disease progression. Monthly Medicare-paid costs were evaluated during the TKI therapy period and following progression. Results: The study included 364 patients. The total mean monthly cost during TKI therapy was $20, 106 (95% confidence interval [CI] = $16, 836–$23, 376), of which 47.0% and 42.4% represented hospitalization costs and anti-cancer therapy costs, respectively. Following progression on TKI therapy (data available for 316 patients), total mean monthly cost was $19, 274 (95% CI = $15, 329–$23, 218), and was higher in the 76.3% of patients who received anti-cancer therapy following progression than in the 23.7% of those who did not ($20, 490 vs $15, 364; p  < .001). Among patients who received it, anti-cancer therapy ($11, 198; 95% CI = $7, 102–$15, 295) represented 54.7% of total mean monthly cost. Among patients who did not receive anti-cancer therapy, hospitalization ($13, 829; 95% CI = $4, 922–$22, 736) represented 90.0% of total mean monthly cost. Impaired performance status and brain metastases were significant predictors of increased cost during TKI therapy. Limitations: The study design may limit the generalizability of findings. Conclusions: Healthcare costs during TKI treatment and following progression appeared to be similar and were largely attributed to hospitalization and anti-cancer therapy. Notably, almost one-quarter of patients did not receive anti-cancer therapy following progression, potentially indicating an unmet need; hospitalization was the largest cost contributor for these patients. Additional effective targeted therapies are needed that could prolong progression-free survival, leading to fewer hospitalizations for EGFR mutation-positive patients.